EFFORTS TO PREVENT BULLIYNG CASES IN DAYAH BORDER MINHAJUSSALAM SUBULUSSALAM CITY - Cut Dewi Rahma Cut Dewi Rahma; Ainal Mardhiah Ainal Mardhiah (Jurnal Ikhtibar Nusantara, 2024)
Bullying cases in the educational environment, including in dayah (pesantren), are a serious problem and have a negative impact on the psychology and social development of santri. This study aims to identify and analyse efforts to prevent bullying cases in Dayah Perbatasan Minhajussalam Subulussalam City. This research uses a qualitative approach with a case study method, which involves in-depth interviews with dayah managers, teachers, students, as well as direct observation in the field. The results showed that bullying prevention efforts in the dayah include several important steps, including: fostering religious morals and ethics through religious teaching that focuses on the values of tolerance and compassion, However, there are still in the implementation of these prevention efforts, such as Many people, including victims and witnesses, do not always realise that they are facing or witnessing acts of bullying.